A finite element model (FEM) for predicting the corrosion of multi‐material coupling system on aircrafts. Issue 11 (14th June 2018) - Chen, Yueliang; Huang, Hailiang; Zhang, Yong; Bian, Guixue; Wang, Chenguang; Wang, Andong
Abstract : An approach based on a finite element model (FEM) is proposed to predict corrosion locations and regions of multi‐material coupling system on aircrafts in solution. In this work, the feasibility of the model is verified by the comparison of the galvanic current and mixed potential between test and simulation values in the multi‐electrode system. This model was applied to the analog connectors commonly used on aircraft. The surface potential distribution was measured by scanning micro‐reference electrode (SMRE) technique. It is found that the simulated potential is basically consistent with the measured potential trend, and the numerical difference is not significant. In terms of the corrosion morphology after 30 d soaking, it can be seen that the corrosion locations and regions are basically consistent with those obtained in the simulated potential distribution over −858 mV, while −858 mV is just the pitting potential of the aluminum alloy. The higher local current distribution in the corrosion concentration area is, the more serious corrosion is, which is in accordance with the experimental results. Abstract : An approach based on a finite element model is proposed to predict corrosion locations and areas of multi‐material coupling system on aircrafts in solution. The feasibility of the model is verified by the comparison of the galvanic current and mixed potential between test value and simulation value in the multi‐electrode system.